Qaryat al‐Fāw/ Qaryatum dhāt Kāhlim: On the identity of the god Kahl - de Lara, J (Wiley, 2024)
Qaryatum dhāt Kāhlim (‘the City of [the god] Kahl’) is the Ancient South Arabian name of the modern site of Qaryat al‐Fāw. This compound refers to the tutelary deity of the city, in this case, a god called Kahl. However, the identity of this Kahl is obscure. Who is this god that makes his appearance in history towards the end of the second half of the first millennium bc? Despite his name being recorded in various texts and inscriptions on numerous objects that confirm his role as the city's patron god, scant information exists regarding his attributes or sphere of influence. Nonetheless, clues on some of his characteristics can be gleaned from coins bearing his likeness. This serves as a springboard for exploring potential connections with iconographies seen in petroglyphs, statues and paintings from the region, suggesting that Kahl may fit within the archetype of the smiting or menacing god, a prevalent motif in the broader Eastern Mediterranean region.